2015
DOI: 10.1007/s11030-015-9572-8
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient water-mediated approach to access benzazoles: metal catalyst and base-free synthesis of 2-substituted benzimidazoles, benzoxazoles, and benzothiazoles

Abstract: An efficient water-catalyzed method has been developed for the synthesis of 2-substituted benzimidazoles, benzoxazoles, and benzothiazoles in one step. The present method excludes the usage of toxic metal catalysts and bases to produce benzazoles in good to excellent yields. An efficient and versatile water-mediated method has been established for the synthesis of various 2-arylbenzazoles. The present protocol excludes the usage of any catalyst and additive provided excellent selectivities and yields with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…This is clearly an alternative to the transition-metal-based synthesis of benzoxazoles. 71 In the same year, Maleki et al studied the synthesis of benzoxazole derivatives 3 from o-aminophenol 2 and several aromatic aldehydes, orthoesters, carboxylic acids, amides, or acyl chlorides through a one-pot condensation in water at room temperature by using Ag@TiO 2 nanocom-posites as the catalyst. 72 As shown in Scheme 42, this method is simple, cost effective, and follows a green pathway for the synthesis of this privileged moiety.…”
Section: Account Syn Lettmentioning
confidence: 99%
“…This is clearly an alternative to the transition-metal-based synthesis of benzoxazoles. 71 In the same year, Maleki et al studied the synthesis of benzoxazole derivatives 3 from o-aminophenol 2 and several aromatic aldehydes, orthoesters, carboxylic acids, amides, or acyl chlorides through a one-pot condensation in water at room temperature by using Ag@TiO 2 nanocom-posites as the catalyst. 72 As shown in Scheme 42, this method is simple, cost effective, and follows a green pathway for the synthesis of this privileged moiety.…”
Section: Account Syn Lettmentioning
confidence: 99%
“…4), confirming the role of K 2 S 2 O 8 is important in initial step (oxidation of benzylamine) as well as in final step (cyclization and oxidation of imine to final product). However, the final oxidation can not be ruled out to proceed either by atmospheric oxygen or sole oxygen dissolved in the water used as reaction solvent . K 2 S 2 O 8 is strong oxidizing agent and catalyze the oxidation of benzylamine to benzaldehyde, and also, reaction at room temperature, excludes the free radical pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Bala et al reported water‐promoted synthesis of 2‐substituted benzothiazoles/benzoxazoles/benzimidazoles in a tandem manner [Eq. (17)].…”
Section: Condensation Of 2‐aminothiophenols With Various Cyclizatimentioning
confidence: 99%